Pd-catalyzed coupling of non-activated dibromoarenes to 2,3-Diaminoarenes: formation of N,N′-Dihydropyrazines - Engelhart, Jens U.; Lindner, Benjamin; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2013)
Accessible azaacenes: Pd-catalyzed coupling reactions between aromatic diamines and unactivated aromatic dibromides furnish N,N′-dihydrodiazapentacenes, -hexacenes, and -heptacenes (see scheme; TIPS=triisopropylsilyl). Oxidation of these products led to diazapentacenes and a diazahexacene. The existence of a diazaheptacene intermediate was proven by solving the single-crystal structure of its (4+4) dimerization product.
Gesehen am 09.02.2021